Електричне поле та електричні сили у спонтанно поляризованому неполярному ізотропному діелектрику - Tomchenko, M. D. (Publishing house "Academperiodika", 2019)
Based on the microscopic Maxwell equations, we develop a method of description of the electric field in a spontaneously polarized isotropic nonpolar dielectric. We find the solution for the electric field E(r) for several typical examples. Moreover, we generalize Helmholtz’s formula for the electric force acting on a volume element of a dielectric with regard for the contribution of the spontaneous polarization.